Improving ferroelectric properties of Pb(Zr0.44Ti0.56)O3ceramics by Pb(Mg1/3Nb2/3)O3addition - Supattra Wongsaenmai (2018)
Ceramics in PMN-PZT system with formula (x)Pb(Mg1/3Nb2/3)O3-(1 - x)Pb(Zr0.44Ti0.56)O3(when x = 0.0, 0.1, 0.3, 0.5, 0.7) are prepared by a solid-state mixed-oxide technique. The phase formation behavior and microstructure are studied using X-ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. The ferroelectric properties are measured by a simple Sawyer-Tower circuit. XRD analysis shows that the possible morphotropic phase boundary (MPB) between the tetragonal and pseudo-cubic phases is identified near the 0.3PMN-0.7PZT composition. In addition, ferroelectric properties of PMN-PZT ceramics are found to enhance at the ceramic composition with x = 0.3. This clearly implies that the MPB of this PMN-PZT system lies near the x = 0.3 composition. Most importantly, this study shows that the addition of PMN can improve the ferroelectric behavior in PZT ceramics. © 2005 Elsevier B.V. All rights reserved.